Financial Literacy Level: An Analysis of Jaipur District Rural Women - Deepika Taparia (Journal of Informatics Education and Research, 2025)
Financial inclusion plays a major role in social and economic empowerment in developing countries such as India. Rural women who were previously facing challenges in accessing formal financial systems are the pioneers of inclusive finance with the help of government programs, technological advancements, and improved literacy. In a bid to determine the financial literacy of rural women, this paper examines the banking habits, knowledge, borrowing behavior, and digital use of women in Jaipur district, Rajasthan. Primary data was collected by a structured questionnaire by fifty respondents. The study indicates that all the participants have a bank account and more than three-fourths of them have accessed credit through official sources. Also, eighty percent of respondents use mobile or UPI banking. The income and educational level are closely related to financial awareness and use of financial services. The paper concludes that focused policies, exposure to technology, and financial education have played a role in increasing financial inclusion. To continue such developments, it proposes to strengthen literacy programs and cyber infrastructure.